2016
DOI: 10.1038/srep27018
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the XPC gene affect urinary bladder cancer risk: a case-control study, meta-analyses and trial sequential analyses

Abstract: Compromised activity of the DNA repair enzymes may raise the risk of a number of cancers. We analyzed polymorphisms in the Xeroderma Pigmentosum, Complementation Group C (XPC) gene for their correlation with urinary bladder cancer. Ala499Val and Lys939Gln polymorphisms were genotyped in 234 urinary bladder cancer cases and 258 control samples. A significant association between Ala499Val polymorphism and bladder cancer was observed (OR = 1.78, CI = 1.19–2.66, p = 0.005); however, Lys939Gln was unrelated (OR = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…A meta-analysis is prone to systematic errors (bias) or random errors (play of chance) due to dispersed data and repeated significance testing [ 100 ]. To obtain more comprehensive assessment, trial sequential analysis (TSA) (version 0.9; Copenhagen Trial Unit, Copenhagen, Denmark, 2011) was used to calculate required information size (number of samples) and to confirm statistical reliability of meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis is prone to systematic errors (bias) or random errors (play of chance) due to dispersed data and repeated significance testing [ 100 ]. To obtain more comprehensive assessment, trial sequential analysis (TSA) (version 0.9; Copenhagen Trial Unit, Copenhagen, Denmark, 2011) was used to calculate required information size (number of samples) and to confirm statistical reliability of meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, those meta-analyses results showed that the XPC Ala499Val polymorphism was not associated with increased risk of most tumors including breast, colorectal, gastric, and lung. However, their results demonstrated that the XPC Ala499Val polymorphism may contribute to susceptibility to bladder cancer, especially among Caucasians (33,34). Moreover, our pooled results showed that this polymorphism is significantly associated with risk of CMM.…”
Section: Subgroupmentioning
confidence: 56%
“…The SNP was also found to be significantly associated with an elevated overall cancer risk in a meta‐analysis (He et al., ). However, two other meta‐analyses have reported a lack of association (Francisco et al., ; Sankhwar et al., ). Therefore, further work in combination with functional characterization of this SNP is needed.…”
Section: Discussionmentioning
confidence: 99%